Melanoma of the sinonasal mucosa: A report on the two cases and a review of the literature - Aleksić, Aleksandra; Gajanin, Radoslav; Djurdjević, Dejan; Novaković, Zorica; Vranješ, Dalibor; Spremo, Slobodan; Travar, Dmitar; Guzina-Golac, Nataša; Tomić-Spirić, Vesna (Vojnosanitetski pregled, 2015)
Introduction. Primary mucosal melanoma of the sinonasal tract is a rare neoplasm, accounting for less than 1% of all melanomas. It has an aggressive and unpredictable biologic behavior characterized by frequent incidence of local recurrence, local and distant metastasis of the disease. Case report. This report summarizes the results of the previous research concerning sinonasal mucosal melanoma, and by the example of the two patients suffering from mucosal melanoma, we described clinical and histopathological features of this rare neoplasm and our experience in its diagnosis and treatment. Conclusion. Only histopathological analysis complemented by immunohistochemical analysis contributes to early and accurate diagnosis of the disease.